Integrasi Dimensi Biopsikososiokultural-Spiritual dalam Pengelolaan Kesehatan Karyawan Industri: Studi Kasus pada Praktik Self-Management Berbasis Makna - Dzul Arsyilana; Rooswanti Putri Adi Agustini; Mohamad Yusak Anshori (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Conventional occupational health programs are often limited to biomedical and administrative approaches, overlooking the psychological, socio-cultural, and spiritual dimensions that empirically drive long-term health adherence. This study aims to analyze how an employee with high cardiovascular risk independently implements a biopsychosocial-cultural-spiritual approach within an organizational context, as well as its implications for human resource management architecture, particularly in employee health management. Using a qualitative case study design, data were collected through in-depth interviews, medical history, and work records of an employee in a cement industry company (36 years old, with 18 years of service). Deductive-abductive thematic analysis revealed four integrative dimensions: (1) biological: self-monitoring and evidence-based lifestyle modification; (2) psychological: transition from denial and perfectionism to acceptance and a meditative state; (3) socio-cultural: social learning from colleagues and neighbors, mentoring as “charitable knowledge sharing,” and reframing corporate KPIs from burdens into sources of support; and (4) spiritual: interpreting illness as a “divine trust” and responsibility as a “khalifah” (steward). The findings indicate that spiritual meaning functions as a catalyst that activates the reallocation of psychological resources (Conservation of Resources Theory), redesigns job demands (JD-R Model), and strengthens perceived benefits within the Health Belief Model. This study contributes to the development of meaning-enabled HRM by shifting the health intervention paradigm from external compliance toward facilitating employees’ holistic agency.